2017
DOI: 10.1186/s12944-017-0602-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and hypolipidemic effects of different parts and formulations of bitter gourd (Momordica Charantia)

Abstract: BackgroundCardiovascular diseases and diabetes are responsible for large number of deaths throughout the globe. Bitter gourd has the potential to become a component of the diet or a dietary supplement for diabetic and pre-diabetic patients owing to the presence of insulin like molecules. Recent investigations have suggested that bitter gourd extracts may ameliorate high fat diet induced obesity and hyperlipidemia in animal models. Moreover, its supplements in food result in lowering weight gain and visceral fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 24 publications
1
19
0
2
Order By: Relevance
“…We recently extended these findings by demonstrating that early dietary supplementation with PMI5011 in male mice protects against the development of insulin resistance and ectopic lipid accumulation in the skeletal muscle and liver independent of any changes in adiposity or body mass [ 26 ]. Momordica charantia , commonly known as bitter melon, has been demonstrated to have anti-hyperglycemic and hypolipidemic [ 27 , 28 ] effects and is a staple of the traditional diet in Okinawa, where rates of mortality and morbidity due to chronic diseases are among the lowest in the world [ 29 ]. Evidence from mechanistic studies in diabetic rodents indicates that bitter melon enhances insulin sensitivity by decreasing serum levels of the pro-inflammatory modulators tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6), decreasing expression of suppressor of cytokine signaling-3 (SOCS-3) and c-Jun N-terminal kinase (JNK), and augmenting insulin-stimulated tyrosine phosphorylation of the insulin receptor substrate-1 (IRS-1) [ 27 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recently extended these findings by demonstrating that early dietary supplementation with PMI5011 in male mice protects against the development of insulin resistance and ectopic lipid accumulation in the skeletal muscle and liver independent of any changes in adiposity or body mass [ 26 ]. Momordica charantia , commonly known as bitter melon, has been demonstrated to have anti-hyperglycemic and hypolipidemic [ 27 , 28 ] effects and is a staple of the traditional diet in Okinawa, where rates of mortality and morbidity due to chronic diseases are among the lowest in the world [ 29 ]. Evidence from mechanistic studies in diabetic rodents indicates that bitter melon enhances insulin sensitivity by decreasing serum levels of the pro-inflammatory modulators tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6), decreasing expression of suppressor of cytokine signaling-3 (SOCS-3) and c-Jun N-terminal kinase (JNK), and augmenting insulin-stimulated tyrosine phosphorylation of the insulin receptor substrate-1 (IRS-1) [ 27 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of reduction was comparable to that of glibenclamide, a conventional medicine used in diabetes treatment. A similar study was carried out by Mahwish et al (2017), in which the hypoglycemic and hypolipidemic effects of different parts of bitter gourd were evaluated in rats. The skin, flesh and whole fruit of bitter gourd were ground into powder and added to normal, high-sucrose and high cholesterol diets, respectively.…”
Section: The Potential Roles Of Vegetables In Diabetes Mellitus Managementmentioning
confidence: 94%
“…[36,113] Saad et al [114] observed that BM has ability to reduce body weight, visceral fat, and the accumulation of high fat due to its antihyperlipidemic effect. Mahwish et al [115] investigated the formulations and the anti-hyperlipidemic and anti-hyperglycemic action of various parts of BM (bitter melon) and observed that BM (bitter melon) has substantial potential in lowering visceral fat, body fat, and also in improving the diabetic complications, consequently showing the anti-hyperlipidemic effects.…”
Section: Antihyperlipidemic Activitymentioning
confidence: 99%